Addressing effective construction logistics through the lens of vehicle movements. Issue 3 (13th May 2014) - Ying, Fei; Tookey, John; Roberti, Johannes
Abstract : Purpose: – Construction logistics is an essential part of construction supply chain management (CSCM). However, limited attention has been paid to this issue in the New Zealand construction industry. The purpose of this paper is to contribute to the knowledge about what hampers efficiency in transporting construction materials and plants to a construction site. The intention is to gain detailed understanding of the practice and obstacles in efficient construction logistics and thus identify interventions to improve logistics efficiency, especially using the numbers of vehicle movements to the construction site as an indicator. Design/methodology/approach: – A case study approach was adopted with on-site observations and interviews. Observations were performed during constructions on-site from the start of construction to "hand-over" to the building owner. A selection of construction suppliers and subcontractors involved in the studied project were interviewed. Findings: – Data analysis suggested that cost-related factors affecting the construction logistics, both monetary and non-monetary factors were not measured and largely ignored, especially the possible environmental and/or social impact occurred by the truck movement. Factors in the service-related sector were insufficiently managed in the observed site. The main contribution to inefficient construction logistics are related to understanding and implementing CSCM. It is noticed that there is inadequate awareness of CSCM and logistics efficiency largely due to lack of commitment from the management level and skills at the operational level. Originality/value: – Significant intrinsic and extrinsic interventions necessary to enhance construction logistics were acknowledged from the data analysis. These include both qualitative and quantitative data. These intrinsic and extrinsic interventions, such as implementing appropriate logistics tools that suits individual site and introducing traffic management costs, offer plausible explanations regarding how to improve the efficiency in construction logistics through optimising transportation movements to the construction site.